2024
DOI: 10.3390/su16020814
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Sand and Aggregates for Structural Concrete: Toward the Industrial Production of High-Quality Recycled Materials with Low Water Absorption

Jan Skocek,
Alexandre Ouzia,
Encarnacion Vargas Serrano
et al.

Abstract: Concrete recycling to produce aggregates is crucial in reducing the demand for virgin materials in the construction industry, particularly for the most widely used building material—concrete. A potential solution to enhance the quality of recycled aggregates involves the removal of the adhered cement paste from their surfaces. In this study, samples of industrial demolished concrete were selectively separated into recycled sands and aggregates while removing the hydrated cement paste. The recycled materials we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In stage 1 of the experiment, different percentages, from 0% to 100%, of RCA concrete were tested by using it in the construction of Samwoh's Eco-Green Building. The final results showed that the compressive strength for low and medium concentrations remained consistent, whereas there was some increase in strength when the percentage of RCA concrete increased [23]. The success of the RCA concrete results could be used to expand building codes to permit the implementation of RCA concrete in the construction industry.…”
Section: Singaporementioning
confidence: 91%
“…In stage 1 of the experiment, different percentages, from 0% to 100%, of RCA concrete were tested by using it in the construction of Samwoh's Eco-Green Building. The final results showed that the compressive strength for low and medium concentrations remained consistent, whereas there was some increase in strength when the percentage of RCA concrete increased [23]. The success of the RCA concrete results could be used to expand building codes to permit the implementation of RCA concrete in the construction industry.…”
Section: Singaporementioning
confidence: 91%
“…This is certainly due to the fact that the hardened cement paste which adheres to the aggregates is porous and its density is lower than that of natural sands and aggregates. For this reason, it was found that the density of the recycled material gradually decreased as the bonded cement content increased (Skocek et al, 2024).…”
Section: Density and Water Absorptionmentioning
confidence: 99%